Zoning of Social Vulnerability for Tidal Flood Disaster in Medan Belawan District, Medan City Based on Remote Sensing and Geographic Information Systems - Budi Rahmah Panjaitan; Lili Somantri; Eka Wulan Safriani; Arifin (United Kingdom) (Tunas Geografi, 2023)
This study aims to 1) identify the social vulnerability of tidal floods in Medan Belawan District and 2) produce a zoning map of social vulnerability to tidal floods in Medan Belawan District descriptive quantitative type research. The variable used refers to Regulation of the Head of BNPB No. 2 of 2012 with changes covering population density, sex ratio, ratio of persons with disabilities, land use, and existing tidal flooding. The social vulnerability variable is then classified using a scoring technique. Data collection techniques in this study were document studies of secondary data obtained from various agencies. The results showed that five urban villages (83%) in Medan Belawan District had high tidal flood social vulnerability, and only one urban town (17%) was classified as having moderate social vulnerability. The urban villages with high tidal flood social vulnerability are Bagan Deli urban village, Belawan Bahagia urban village, Belawan Bahari urban village, Belawan I urban village, and Belawan II urban village. Meanwhile, the urban village with a moderate level of social vulnerability to tidal floods is the Belawan Sicanang Village. Belawan I Village occupies the highest tidal flood social vulnerability class, and the lowest tidal flood social vulnerability class is populated by Belawan Sicanang urban village.Keywords: Social Vulnerability, Tidal Flood, DisasterÂ